Media and Cultural Industries Internships: A Thematic Review and Digital Labor Parallels - Thomas Corrigan (tripleC: Communication, Capitalism & Critique)
This article reviews existing research on the motivations and experiences of interns in media and cultural industries. Digital labour theories are used to organize and make sense of the existing internship literature. Throughout the article, parallels are also drawn between the experiences of interns and those of digital creative labourers—both professionals and peer producers. Three key themes are identified within the internship literature: 1) interns derive satisfaction from work they con- sider meaningful, particularly hands-on work executed under the training and trust of effective supervisors; 2) interns see their work as future-oriented investments in their skills, professional networks, and personal brands; and 3) the ambiguity and professional necessity of media and cultural industries internships make them fertile ground for exploitation and self-exploitation. In conclusion, I argue that attentiveness to meaning, temporality, and ambiguity will be essential to future critical investigations of internships.